O METODZIE INTERPRETACJI PRZEPISÓW PRAWA KARNEGO - Zawłocki, Robert (Wydział Prawa i Administracji UAM, 2004)
The article concerns the correct method of interpreting criminal regulations. There is no doubt that the way of criminal interpretation directly influences its result. Therefore, the issue is considered as one of the most important problems in the criminal law. According to W. Wolter, representing in this matter the classical view, the act of an explanation of the criminal regulations should be based only on the logic and language rules (dogmatic way of criminal interpretation). And for his opponent, I. Andrejew, the aforesaid operation should be complemented with an explanation based on the special dynamic element, connected whit present criminal policy requirements (social needs). His view of criminal interpretation is based on functional explanation of criminal regulations. The author of the article shows both sides’ arguments and, at the end, proposes his own opinion in accordance with the dynamic interpretation.
ON METHOD OF INTERPRETING CRIMINAL REGULATIONS